Identifikasi Kesalahan Siswa Dalam Menyelesaikan Soal Tipe Hots (Higher Order Thinking Skill) Materi Operasi Aljabar Di SMP Muhammadiyah 4 Palembang (Universitas Muhammadiyah Palembang, 2023)
Many students still need to improve, causing low student learning outcomes. This study aimed to find out what mistakes students made in solving the Hots (Higher Order Thinking Skill) type questions on algebraic operations material at SMP Muhammadiyah 4 Palembang. This research is a qualitative descriptive study. The data collection technique is in the form of giving as many as five test questions. Based on the research results, the mistakes made by students in solving HOTS (Higher Order Thinking Skill) type questions in algebraic material are conceptual and procedural errors. Concept errors occur in each item, with the percentage of errors that occur, namely item number 1 at 33.3%, number 2 at 23.3%, number 3 at 16.7%, number 4 at 16.7%, number 5 at 26.7%. The average percentage of students' conceptual errors is 23.34%. Procedural errors occur in each item, with the percentage of errors that occur, namely item number 1 of 10%, 2 of 20%, 3 of 33.3%, 4 of 26.7%, and 5 of 16.7 %. The average percentage of procedural errors made by students is 21.34%.